The Use of Video Annotation Tools and Informal Online Discussions to Explore Preservice Teachers' Self- and Peer-Evaluation of Academic Feedback. Issue 1 (January 2021) - Zaier, Amani; Arslan-Ari, Ismahan; Maina, Faith
This study explored the quality of preservice teachers' self- and peer-academic feedback using video annotation tools to capture their teaching practices. They were also provided with an informal online discussion board as part of the peer support system. Twenty-five preservice teachers at a large university in the Southwestern United States volunteered to participate in this study. Data revealed a striking difference between self-evaluation and peer-evaluation. Preservice teachers rated themselves considerably higher compared with their peer-evaluation. The quality of the academic feedback and evaluation remained at the surface level with a mismatch between areas of refinement and areas of reinforcement. Evidence-based feedback and constructive criticism for areas of refinement were openly given during the informal discussion forums. Despite the inconsistency, preservice teachers perceived online communication through discussion posts as a valuable source of building relationships and providing support system.